Shifting Ground. A Socially Engaged Immigrant Outreach Project Working with Creative Processes and Cultural Sustainability. - Gilmor, Jane (2019)
his catalog documents both the process and the products of the Shifting Ground workshops, which became a way to share life stories and cultural knowledge while also creating closer ties among us. We sin- cerely hope Shifting Ground gives visibil- ity and voice, in a digniied way, to recent immigrants to Cedar Rapids while also promoting public art that beneits both the local community and those marginal- ized from it. Most importantly, we want to thank all our participants, without whom this project would not have been possible.